Pallisentis kalriai, New Species (Acanthocephala Quadrigyridae) from the fish Labeo rohita of Kalri Lake, Sind, Pakistan - Khan, Aly; Bilqees, Fatima Mujib (1985)
A new species Pallisentis Kalriai is described from the fish Labeo rohita from Kalri Lake Sind. The new species is characterized by possessing medium body size 40 proboscis hooks (4 rows of 10 hooks), short invaginable proboscis, a collar of spines consisting of 15 rows of 20 spines each, poorly developed uterine bell, clindrical testis, spines in anterior third of the body, thin-walled oval eggs measuring 0.032-0.036 by 0.012-0.016mm. This is the second record of the genus from Pakistan.
Includes bibliographical references (pages 105-106) and index.
Keywords: Zoology; Pallisentis kalriai -- Description